Photocatalytic CO2 reduction by CdS promoted with a zeolitic imidazolate framework - Wang, Sibo; Wang, Xinchen (Applied catalysis. B, Environmental, 2015)
•Photocatalytic CO2 reduction by the cooperation of Co-ZIF-9 and CdS was studied under mild reaction conditions.•The Co-ZIF-9/CdS can efficiently photocatalyze CO2 conversion to CO with visible light, affording a high apparent quantum yield of 1.93%.•The Co-ZIF-9 acts as a co-catalyst to enhance CO2 adsorption and to promote charge separation kinetics on the CdS photocatalysts. Metal organic frameworks (MOFs) have emerged as a new class of multifunctional porous materials, and more particularly the family of zeolitic imidazolate frameworks (ZIFs) have shown great promise in the applications of carbon dioxide capture and storage. The CO2 photoreduction system was established by employing CdS semiconductor and Co-ZIF-9 to act as a catalyst and a cocatalyst, respectively. This hybrid system cooperating with bipyridine and triethanolamine exhibits high catalytic activity in the deoxygenative conversion of CO2 to CO under visible light irradiation at mild reaction conditions. 13CO2 isotopic experiment validated that the produced CO was from the photoreduction of CO2, instead of organics in the system. The effect of parameters such as cocatalyst concentration, reaction temperature, solvent properties, and water effect were investigated in details. Under the optimized reaction conditions, a high apparent quantum yield of 1.93% was achieved under monochromatic irradiation of 420nm. The uniqueness of Co-ZIF-9 in supporting CdS for CO2 reduction reaction was explored by comparing its catalytic functions with other MOFs. In-situ photoluminescence and photocurrent generation measurements demonstrated the function of Co-ZIF-9 for promoting electron transfers. At last, a possible reaction mechanism of the photoreduction reaction was proposed.